DISTRIBUTION OF HEAVY METALS IN SOME VEGETABLES GROWN IN THE VICINITY OF LEAD AND ZINC SMELTER PLANT - Pančevski, Zlatko; Stafilov, Trajče; Bačeva, Katerina (Macedonian Academy of Sciences and Arts, 2017)
Gardens near the lead and zinc smelter plant "Zletovo" in the town of Veles, Republic of Macedonia, are the main suppliers with vegetables and fruits for the residents of this town. This area, was exposed thirty years to high environmental contamination with heavy metals (Cd, Pb and Zn). The smelter plant was a major source of heavy met-als pollution in the environment, including the garden soils used for the production of vegetables and fruits. The aim of this study is to determine the level of contamination (especially with Cd, Pb and Zn) in green garlic (Allium sa-tivum) and green onion (Allium scallion) produced on the contaminated soil and to determine its level of accumula-tion in the plants. The contents of 21 elements (Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Pb, Sr, V and Zn) in the vegetables and corresponding soils were analyzed by inductively coupled plasma – atomic emis-sion spectrometry (ICP-AES) after microwave digestion. It was found that the contents of Cd, Pb and Zn in the vege-tables from all of the four studied gardens is over the maximum permissible level according to the Macedonian regu-lations. The content of Cd in washed green garlic samples ranges from 0.60 to 2.70 mg kg–1, for Pb from 4.30 to 6.14 mg kg–1 and for Zn from 11.7 to 29.9 mg kg–1, while their contents in the washed green onion samples ranges from 0.77 to 2.66 mg kg–1 for Cd, from 3.98 to 5.35 mg kg-1 for Pb and from 21.2 to 38.0 mg kg–1 for Zn.